The Effect of Sacubitril/Valsartan Treatment on Cardiac and Renal Functions of a Patient With Cardiorenal Syndrome Type 4 and Stage 5 CKD After More Than Three Years of Follow-Up - Cheng, Shuiqin; Zhou, Tingting; Yu, Le; Chen, Yunmin; Zhang, Zhihong; Wang, Jinquan; Yu, Yusheng (Frontiers in Medicine, 2022)
It is difficult to treat cardiorenal syndrome (CRS) in clinical practice, which is the common reason for the death of patients. This report aimed to describe the effects of sacubitril/valsartan treatment on cardiac and renal functions of a patient with cardiorenal syndrome type 4 (CRS4) after more than 3 years of follow-up. A 77-year-old Chinese woman was admitted to our hospital because of CRS4 and stage 5 chronic kidney disease (CKD), who had a history of long-term proteinuria and renal failure. The patient’s cardiothoracic ratio (CTR) measured by chest X–ray was 0.6. Cardiac ultrasonography showed that the left ventricular ejection fraction (LVEF) was 0.40. The patient had been treated for heart failure (HF) for 5 months, but the clinical manifestations were not improved, and the renal function gradually deteriorated. In our hospital, she received sacubitril/valsartan treatment for at least 40 months. The symptoms of HF were relieved, and the indices of cardiac function were improved. In addition, the patient’s renal function was stable. During the treatment, the dosage of sacubitril/valsartan needed to be adjusted to achieve the optimal therapeutic effect. Follow-up results showed that she achieved cardiac function of New York Heart Association (NYHA) class Ⅱ with an ejection fraction of 0.60 and E/A > 1 indicated by echocardiogram, and did not develop hyperkalemia. In summary, the improvement of cardiac and renal functions of the CRS4 patient was associated with the long-term sacubitril/valsartan treatment.